Ethnobotany, ethnopharmacology and toxicity of Geranium ayavacense Willd. ex Kunth and Geranium sessiliflorum Cav. (Geraniaceae): A Review - Velasquez-Arevalo, Sharon; Ramirez, J-Kenedy; Rodríguez-Silva, Cristhian; Villarreal-La Torre, Víctor (Ethnobotany Research and Applications, 2020)
Background: Around the world, species of the genus Geranium have been used since ancient times, including Geranium ayavacense and Geranium sessiliflorum which, due to their diverse medicinal properties, are even dispensed in health establishments. Both species have several common names, being "pasuchaca" the name most used to refer to them; This could lead to identification confusion and even tampering issues. Therefore, this review aims to analyze and contrast the medicinal use with the therapeutic effect, in order to identify the scientific gaps on these two plant species. Methods: The relevant information was obtained through systematic searches, in databases such as Scopus, ScienceDirect and PubMed. In addition, information from primary sources not covered by these was included, such as thesis repositories. The data was analyzed and organized according to geographic distribution, botanical aspects, traditional use, phytochemistry, ethnopharmacology and toxicity. Results: A total of 20 studies on these plants were documented, most of them ethnobotanical. The plant, fresh or dried, is used as a decoction or infusion. The use of Geranium ayavacense as a hypoglycemic and antibacterial has more evidence; while Geranium sessiliflorum was studied for its antibacterial activity. However, there are scientific gaps with respect to other therapeutic properties conferred by traditional medicine. Conclusions: Despite the scarce scientific information available, these plants are widely used, a situation that could even put the health of the people who use them at risk; For this reason, it is essential to carry out more in-depth studies, with a phytochemical, pharmacological and toxicological approach.